Income Generation and Social Protection for the Poor - World Bank (Washington, DC, 2012)
This report summarizes and consolidates the findings of three Bank studies on poverty issues in Mexico, written as part of the second phase of this work: Urban Poverty, Rural Poverty, and Social Protection. It also expands on how Mexico will seek to use social protection policy as a vehicle for redistribution. Discussed in Chapter 1, the state has a clear role in providing risk-pooling mechanisms where private insurance markets fail (e.g., old age and health insurance), but the role of social protection policy in promoting redistribution is more an issue of national choice. That choice, however, has clear consequences for equity and poverty reduction outcomes. The economic trade?off between growth and equity, and thus between growth and redistribution, has been refuted by both theoretical advances, and international experience in recent years. International experience points to examples where redistribution has been achieved in a wide variety of ways. The choice is two fold: how much distribution; and through which means. The relative importance given to redistribution, and the role assigned to the social protection system in achieving equity objectives is a question of national objectives, but is crucial to guiding the direction of social protection policy reform. To summarize, the report finally focuses on four key emerging issues within social protection in Mexico: a) social security reform, b) health risks among the poor, c) old age poverty, and, d) the need to balance public risk management mechanisms with a more integrated strategy to combat chronic poverty. In order to tackle these challenges, Mexico faces a range of political choices.